Consequences of ccmR deletion on respiration, fermentation and H2 metabolism in cyanobacterium Synechococcus sp. PCC 7002. Issue 7 (28th January 2016) - Krishnan, Anagha; Zhang, Shuyi; Liu, Yang; Tadmori, Kinan A.; Bryant, Donald A.; Dismukes, Charles G.
ABSTRACT: CcmR, a LysR‐type transcriptional regulator, represses the genes encoding components of the high‐affinity carbon concentration mechanism in cyanobacteria. Unexpectedly, deletion of the ccmR gene was found to alter the expression of the terminal oxidase and fermentative genes, especially the hydrogenase operon in the cyanobacterium Synechococcus sp . PCC 7002. Consistent with the transcriptomic data, the deletion strain exhibits flux increases (30–50%) in both aerobic O2 respiration and anaerobic H2 evolution. To understand how CcmR influences anaerobic metabolism, the kinetics of autofermentation were investigated following photoautotrophic growth. The autofermentative H2 yield increased by 50% in the CcmR deletion strain compared to the wild‐type strain, and increased to 160% (within 20 h) upon continuous removal of H2 from the medium ("milking") to suppress H2 uptake. Consistent with this greater reductant flux to H2, the mutant excreted less lactate during autofermentation (NAD(P)H consuming pathway). To enhance the rate of NADH production during anaerobic metabolism, the ccmR mutant was engineered to introduce GAPDH overexpression (more NADH production) and LDH deletion (less NADH consumption). The triple mutant ( ccmR deletion + GAPDH overexpression + LDH deletion) showed 6–8‐fold greater H2 yield than the WT strain, achieving conversion rates of 17 nmol 10 8 cells −1 h −1 and yield of 0.87 H2 per glucose equivalent (8.9% theoretical maximum). Simultaneous monitoring of the intracellular NAD(P)H concentration and H2 production rate by these mutants reveals an inverse correspondence between these variables indicating hydrogenase‐dependent H2 production as a major sink for consuming NAD(P)H in preference to excretion of reduced carbon as lactate during fermentation. Biotechnol. Bioeng. 2016;113: 1448–1459. © 2015 Wiley Periodicals, Inc. Abstract : The deletion of the ccmR gene, important for carbon uptake, in cyanobacterium Synechococcus 7002, alters the expression of multiple fermentative genes, especially that of the hydrogenase operon and the associated maturases involved in the fermentative H2 evolution. Using targeted metabolic engineering of the CcmR deletion strain, the authors report the generation of a mutant strain capable of producing 6–8‐fold higher H2 than the WT.